Identification of preclinical Alzheimer's disease by a profile of pathogenic proteins in neurally derived blood exosomes: A case‐control study. Issue 6 (14th August 2014) - Fiandaca, Massimo S.; Kapogiannis, Dimitrios; Mapstone, Mark; Boxer, Adam; Eitan, Erez; Schwartz, Janice B.; Abner, Erin L.; Petersen, Ronald C.; Federoff, Howard J.; Miller, Bruce L.; Goetzl, Edward J.
Abstract: Background: Proteins pathogenic in Alzheimer's disease (AD) were extracted from neurally derived blood exosomes and quantified to develop biomarkers for the staging of sporadic AD. Methods: Blood exosomes obtained at one time‐point from patients with AD (n = 57) or frontotemporal dementia (FTD) (n = 16), and at two time‐points from others (n = 24) when cognitively normal and 1 to 10 years later when diagnosed with AD were enriched for neural sources by immunoabsorption. AD‐pathogenic exosomal proteins were extracted and quantified by enzyme‐linked immunosorbent assays. Results: Mean exosomal levels of total tau, P‐T181‐tau, P‐S396‐tau, and amyloid β 1–42 (Aβ1–42) for AD and levels of P‐T181‐tau and Aβ1–42 for FTD were significantly higher than for case‐controls. Step‐wise discriminant modeling incorporated P‐T181‐tau, P‐S396‐tau, and Aβ1–42 in AD, but only P‐T181‐tau in FTD. Classification of 96.4% of AD patients and 87.5% of FTD patients was correct. In 24 AD patients, exosomal levels of P‐S396‐tau, P‐T181‐tau, and Aβ1–42 were significantly higher than for controls both 1 to 10 years before and when diagnosed with AD. Conclusions: Levels of P‐S396‐tau, P‐T181‐tau, and Aβ1–42 in extracts of neurally derived blood exosomes predict the development of AD up to 10 years before clinical onset.